2020
DOI: 10.1101/2020.03.24.20042366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of Chloroquine and Hydroxychloroquine in the Treatment of COVID-19 Infection- A Systematic Literature Review

Abstract: Background: Coronavirus pandemic is currently a global public health emergency. At present, no pharmacological treatment is known to treat this condition, and there is a need to review the available treatments.Objective: While there have been studies to describe the role of chloroquine and hydroxychloroquine in various viral conditions, there is limited information about the use of them in COVID-19. This systematic review aims to summarize the available evidence regarding the role of chloroquine in treating co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…The rst reports recommending HCQ as an effective treatment for SARS-CoV-2 infection have been under increased scrutiny due to questionable methodologies and outcomes [13,19,27,28]. Our results support the negative studies on the prophylaxis and e cacy of HCQ therapy.…”
Section: Discussionsupporting
confidence: 72%
“…The rst reports recommending HCQ as an effective treatment for SARS-CoV-2 infection have been under increased scrutiny due to questionable methodologies and outcomes [13,19,27,28]. Our results support the negative studies on the prophylaxis and e cacy of HCQ therapy.…”
Section: Discussionsupporting
confidence: 72%
“…This is in agreement with the other authors with similar findings of lack of literature in this regard. 28,29,30,46 The earliest nonempirical evidence came from China in form of report letter in which more than 100 patients with COVID pneumonia showed clinical improvement and changes in image findings on chloroquine administration. 43 It is pertinent to note that this letter was the brief report of ongoing many trials in various locations in China, neither it mentioned any specific data regarding interventions, study design, study population and outcome measures, nor any adverse events were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine and hydroxychloroquine are viewed today as the most promising anti-COVID-19 drugs [71,72,78,79]. One could apprehend that melatonin would interfere with them because it was reported that the anti-malaria effectiveness of chloroquine was greatly increased by a melatonin antagonist, Luzindole, and/or bright light at night, which reduced melatonin production.…”
Section: Melatonin Can Be Utilized In Combinations With Drugs and Trementioning
confidence: 99%